Status Hukum Hak Atas Tanah Ulayat Antara Masyarakat Besipae dan Pemerinta Kabupaten Timor Tengah Selatan - Mariano Hermando Boymau; Florensiana Resi Ngepi; Benediktus Peter Lay (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Ulayat rights are a unity with the legal community, especially in the Pubabu community, which will place these rights in their proper place, especially in the Indonesian state, this is stated in Article 3 of UUPA No. 5 of 1960.Ulayat rights are customary rights based on customary law that have been practiced for generations. The research method that the author uses is the normative juridical research method. This research uses a statutory approach problem (Statute-Approach) related to what the researcher wants to examine. The data and information of this research are primary and secondary data which are data that have been available through laws, journals, books, and other factual supporting sources. Regarding the legal status of customary land in besipae by the people who inhabit the area can be said to be uncertain due to several things that become obstacles in the process of finding the legal status of customary land because the ownership status of the land is still uncertain. In other words, these three rights have the same status and superiority, and do not harm each other. In order to maintain a balance between the rights of indigenous peoples and the public interest, the Indonesian government has an obligation to protect the rights of indigenous peoples related to their customary land. Therefore, there is a need for coordination and dialogue between the government, indigenous peoples, and other stakeholders to reach a mutually beneficial and fair agreement in the management of customary land and government land tenure rights.